Major venous thrombosis: a complication of transvenous pacemaker electrodes. - Krug, H (1980)
Two patients with transvenous permanent pacemakers developed thrombosis and occlusion of the superior vena cava around a broken pacing wire, with clot extending into the innominate, subclavian, and axillary veins. Both patients had symptoms and signs of the superior vena cava syndrome which failed to resolve despite anticoagulant and thrombolytic treatment. Obstruction to venous flow, however, was relieved in large measure by the development of collateral venous channels. One of the patients has shown mild symptoms for two years and the other for two months of follow-up. It is suggested that anticoagulant prophylaxis should be given to all patients with a broken wire which cannot easily be removed.